Quantifying the burden of stillbirths before 28 weeks of completed gestational age in high-income countries: a population-based study of 19 European countries. Issue 10158 (3rd November 2018) - Smith, Lucy K; Hindori-Mohangoo, Ashna D; Delnord, Marie; Durox, Mélanie; Szamotulska, Katarzyna; Macfarlane, Alison; Alexander, Sophie; Barros, Henrique; Gissler, Mika; Blondel, Béatrice; Zeitlin, Jennifer; ,; et al.
Summary: Background: International comparisons of stillbirth allow assessment of variations in clinical practice to reduce mortality. Currently, such comparisons include only stillbirths from 28 or more completed weeks of gestational age, which underestimates the true burden of stillbirth. With increased registration of early stillbirths in high-income countries, we assessed the reliability of including stillbirths before 28 completed weeks in such comparisons. Methods: In this population-based study, we used national cohort data from 19 European countries participating in the Euro-Peristat project on livebirths and stillbirths from 22 completed weeks of gestation in 2004, 2010, and 2015. We excluded countries without national data for stillbirths by gestational age in these periods, or where data available were not comparable between 2004 and 2015. We also excluded those countries with fewer than 10 000 births per year because the proportion of stillbirths at 22 weeks to less than 28 weeks of gestation is small. We calculated pooled stillbirth rates using a random-effects model and changes in rates between 2004 and 2015 using risk ratios (RR) by gestational age and country. Findings: Stillbirths at 22 weeks to less than 28 weeks of gestation accounted for 32% of all stillbirths in 2015. The pooled stillbirth rate at 24 weeks to less than 28 weeks declined from 0·97 to 0·70 per 1000 births from 2004 to 2015, a reduction of 25% (RR 0·75, 95% CI 0·65–0·85). The pooled stillbirth rate at 22 weeks to less than 24 weeks of gestation in 2015 was 0·53 per 1000 births and did not significantly changed over time (RR 0·97, 95% CI 0·80–1·16) although changes varied widely between countries (RRs 0·62–2·09). Wide variation in the percentage of all births occurring at 22 weeks to less than 24 weeks of gestation suggest international differences in ascertainment. Interpretation: Present definitions used for international comparisons exclude a third of stillbirths. International consistency of reporting stillbirths at 24 weeks to less than 28 weeks suggests these deaths should be included in routinely reported comparisons. This addition would have a major impact, acknowledging the burden of perinatal death to families, and making international assessments more informative for clinical practice and policy. Ascertainment of fetal deaths at 22 weeks to less than 24 weeks should be stabilised so that all stillbirths from 22 completed weeks of gestation onwards can be reliably compared. Funding: EU Union under the framework of the Health Programme and the Bridge Health Project.